Communal Intimacy and the Violence of Politics : Understanding the War on Drugs in Bagong Silang, Philippines - Jensen, Steffen; Hapal, Karl, 1987- (Book collections on Project MUSE., 2022)
"Explores the war on drugs in the Philippines from below. Rather than seeking to understand the motivations of Duterte's drug war, we explore how it folded itself into communal and intimate spheres in one Manila neighborhood, Bagong Silang"--